Evaluation of chemical properties of Iraqi coastal water, North- western Arabian Gulf - Hussein, Dhor; Alshawi, Imad (Iraqi Journal of Aquaculture, 2026)
This study aims to evaluate the chemical characteristics of Iraqi coastal waters in the northwestern Arabian Gulf for the year 2025, with a focus on the distribution of chemical elements, nutrients, and the environmental and anthropogenic factors controlling them. The significance of the research lies in its attempt to establish a national baseline for the oceanographic properties of Iraqi waters, thereby supporting sustainable marine resource management strategies and monitoring environmental changes.The study area covered a coastal strip of 60 km², where five strategic stations were selected, extending from Khor Al-Zubair to offshore waters. The Ocean Data View (ODV) program was employed to spatially represent the data.The results revealed clear variability in chemical properties: pH values ranged between 7.18 and 7.36, with the lowest values recorded at the inner stations due to port activities and carbon emissions. Station S1 exhibited the highest dissolved oxygen concentration (16.5 mg/L) and the highest carbon dioxide level (20 mg/L), reflecting the influence of ship movements and organic matter decomposition in the inner zones. Total dissolved solids (TDS) peaked at 32 ppm, while chloride concentrations reached 34,741 mg/L at the inner stations, gradually decreasing outward due to mixing with Gulf waters.Regarding nutrients, transitional stations recorded the highest nitrite values, whereas silica peaked (6.528 mg/L) at the inner stations, reflecting the impact of clayey sediments transported from the Shatt Al-Arab.The study concludes that inner and transitional stations are the most affected by human activities and riverine inputs, while offshore stations exhibit lower pollutant concentrations due to dilution processes. The strategic importance of these findings lies in providing accurate indicators of ocean acidification and oxygen depletion, underscoring the need to strengthen environmental monitoring networks to safeguard biodiversity and address climate challenges in the Iraqi coastal zone.